Identification of New Factors Modulating Adhesion Abilities of the Pioneer Commensal Bacterium Streptococcus salivarius - Couvigny, Benoit; Kulakauskas, Saulius; Pons, Nicolas; Quinquis, Benoit; Abraham, Anne-Laure; Meylheuc, Thierry; Delorme, Christine; Renault, Pierre; Briandet, Romain; Lapaque, Nicolas; Guédon, Eric (Frontiers in Microbiology, 2018)
Biofilm formation is crucial for bacterial community development and host colonization by Streptococcus salivarius, a pioneer colonizer and commensal bacterium of the human gastrointestinal tract. This ability to form biofilms depends on bacterial adhesion to host surfaces, and on the intercellular aggregation contributing to biofilm cohesiveness. Many S. salivarius isolates auto-aggregate, an adhesion process mediated by cell surface proteins. To gain an insight into the genetic factors of S. salivarius that dictate host adhesion and biofilm formation, we developed a screening method, based on the differential sedimentation of bacteria in semi-liquid conditions according to their auto-aggregation capacity, which allowed us to identify twelve mutations affecting this auto-aggregation phenotype. Mutations targeted genes encoding (i) extracellular components, including the CshA surface-exposed protein, the extracellular BglB glucan-binding protein, the GtfE, GtfG and GtfH glycosyltransferases and enzymes responsible for synthesis of cell wall polysaccharides (CwpB, CwpK), (ii) proteins responsible for the extracellular localization of proteins, such as structural components of the accessory SecA2Y2 system (Asp1, Asp2, SecA2) and the SrtA sortase, and (iii) the LiaR transcriptional response regulator. These mutations also influenced biofilm architecture, revealing that similar cell-to-cell interactions govern assembly of auto-aggregates and biofilm formation. We found that BglB, CshA, GtfH and LiaR were specifically associated with bacterial auto-aggregation, whereas Asp1, Asp2, CwpB, CwpK, GtfE, GtfG, SecA2 and SrtA also contributed to adhesion to host cells and host-derived components, or to interactions with the human pathogen Fusobacterium nucleatum. Our study demonstrates that our screening method could also be used to identify genes implicated in the bacterial interactions of pathogens or probiotics, for which aggregation is either a virulence trait or an advantageous feature, respectively.